ASPECTS OF THE STUDY OF EMOTIONS IN LINGUISTICS. TILSHUNOSLIKDA HIS-TUYG'ULARNI O'RGANISHNING ASPEKTLARI АСПЕКТЫ ИЗУЧЕНИЯ ЭМОЦИЙ В ЛИНГВИСТИКЕ. - Anora Abduraimova (Western European Studies, 2024)
In exploring the study of emotions in linguistics, this article aims to elucidate the crucial aspects that shape how emotions are expressed, perceived, and communicated through language. By adopting the AIMRAD framework, this article delves into the role of language in reflecting and influencing emotional experiences, the nuances of emotional discourse, and the intersection of emotions with linguistic pragmatics and cultural perspectives
Keywords: Discourse; cross-cultural perspectives; emotional discourse